Pengaruh Budaya FoMO (Fear of Missing Out) terhadap Adaptasi Sosial pada Mahasiswa Rantau - Sabrina Zakiyatun Nisa; Durrotun Nafisah; Filbert Awali M. Hakim; Arfin Nurma Halida (Universitas Kristen Maranatha, 2025)
This study aims to analyze the influence of the Fear of Missing Out (FoMO) culture on the social adaptation of students from outside the region at Universitas Negeri Surabaya. Through a quantitative approach using simple regression analysis, the study involved 213 first-year Psychology students from outside the area as the sample. The results of the analysis indicate that there is no significant influence between FoMO levels and the social adaptation capabilities of these students. This finding suggests that although FoMO has the potential to affect psychological well-being, it does not directly hinder or enhance social integration in a new environment. This research provides important insights into how digital cultures like FoMO may not play a dominant role in influencing individual social adaptation processes in new settings.